Amino Acids Composition In Irrigated And Typical Grey Soils - B. Khalimov; N. Raupova; B. Salimov (Zien Journals, 2025)
In our republic, large-scale theoretical and practical research is being carried out on restoring and preserving the fertility of protected, fallow and irrigated soils, improving soil processes, and achieving certain results. The Strategy for the Development of Agriculture of the Republic of Uzbekistan for 2020- 2030 states that "... Of the 20.2 million hectares of land intended for agriculture, only 20.7 percent are irrigated lands. Over the past 15 years, the area of irrigated land per capita has decreased by 24 percent (from 0.23 to 0.16 ha), rational use of natural resources, including rational use of land and water resources, forest resources, and improvement of the environmental protection system" are identified as important strategic tasks 1 . Based on these tasks, it is important to determine the current ecological and reclamation status of irrigated lands, apply resource-saving agrotechnologies aimed at improving their humus content and biological activity, compile maps of soil salinity and biological activity of the soil, and implement agrotechnical measures based on this.
Keywords: measures; activity; status; resource